OX40L blockade is therapeutic in arthritis, despite promoting osteoclastogenesis - Findlay, Emily Gwyer; Danks, Lynett; Madden, Jodie; Cavanagh, Mary M.; McNamee, Kay; McCann, Fiona; Snelgrove, Robert J.; Shaw, Stevan; Feldmann, Marc; Taylor, Peter Charles; Horwood, Nicole J.; Hussell, Tracy (Proceedings of the National Academy of Sciences - PNAS, 2014)
An immune response is essential for protection against infection, but, in many individuals, aberrant responses against self tissues cause autoimmune diseases such as rheumatoid arthritis (RA). How to diminish the autoimmune response while not augmenting infectious risk is a challenge. Modern targeted therapies such as anti-TNF or anti-CD20 antibodies ameliorate disease, but at the cost of some increase in infectious risk. Approaches that might specifically reduce autoimmunity and tissue damage without infectious risk would be important. Here we describe that TNF superfamily member OX40 ligand (OX40L; CD252), which is expressed predominantly on antigen-presenting cells, and its receptor OX40 (on activated T cells), are restricted to the inflamed joint in arthritis in mice with collagen-induced arthritis and humans with RA. Blockade of this pathway in arthritic mice reduced inflammation and restored tissue integrity predominantly by inhibiting inflammatory cytokine production by OX40L-expressing macrophages. Furthermore, we identify a previously unknown role for OX40L in steady-state bone homeostasis. This work shows that more targeted approaches may augment the “therapeutic window” and increase the benefit/risk in RA, and possibly other autoimmune diseases, and are thus worth testing in humans.